Review of 3‐year outcomes of a very‐low‐energy diet‐based outpatient obesity treatment programme. Issue 2 (3rd February 2016) - Sumithran, P.; Prendergast, L. A.; Haywood, C. J.; Houlihan, C. A.; Proietto, J.
Summary: Obesity is a complex disorder that requires a multidisciplinary treatment approach. This review evaluated 3‐year outcomes of a very‐low‐energy diet (VLED)‐based programme at a tertiary hospital multidisciplinary weight management clinic. Medical records of all patients who agreed to undertake the VLED programme and who did not undergo bariatric surgery during the 3‐year follow‐up period were examined. Baseline data collection included demographic and anthropometric characteristics, childhood onset of obesity and co‐existing medical conditions. Weight was modelled using a linear mixed effects analysis. Logistic regression analyses were used to model the probability of continuing to attend the clinic and to identify pre‐treatment factors associated with longer duration of attendance. Data from 1109 patients were included. A total of 231 patients (19.2%) were still attending the clinic 3 years after their initial appointment. Mean weight loss among patients who attended the clinic for 3 years was 6.4 kg (3.5%, 95% confidence interval [CI] 2.8, 4.2%). People who were prescribed pharmacotherapy maintained greater weight loss at 3 years (7.7% vs. 2.3% without pharmacotherapy, 95% CI for difference 3.9, 7.0%). People who had an onset of obesity in childhood, who had co‐existing hypertension or coronary artery disease, and who did not currently smoke were more likely to continue to attend the clinic for up to 3 years. In summary, in an outpatient weight management clinic, patients who undertook a VLED‐based programme and continued in follow‐up achieved a clinically significant weight loss at 3 years, particularly if pharmacotherapy was used for weight loss maintenance.